2015
DOI: 10.1002/jez.1905
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte responses to in vitro freezing and β‐adrenergic stimulation: Insights into the extreme freeze tolerance of subarctic Rana sylvatica

Abstract: The wood frog, Rana sylvatica LeConte 1825, is a freeze-tolerant amphibian widely distributed in North America. Subarctic populations of this species can survive experimental freezing to temperatures below -16 °C, whereas temperate populations tolerate freezing only at temperatures above -6 °C. We investigated whether hepatocytes isolated from frogs indigenous to Interior Alaska (subarctic) or southern Ohio (temperate) had distinct characteristics that could contribute to this variation in freeze tolerance cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Instead, new cryopreservation methods should look to nature for inspiration. Various species of vertebrates, such as Rana sylvatica (the wood frog), achieve a thermodynamically stable, noninjurious frozen state at high subzero storage temperatures ranging from −6 to −22 °C. Using cryomicroscopic analysis, researchers have detailed the mechanisms of ice propagation utilized by freeze-tolerant wood frogs in nature . In this study, micrographs of liver slices showed continuous ice formed along the vasculature with the parenchyma remaining ice-free and considerably shrunken because of cellular dehydration.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Instead, new cryopreservation methods should look to nature for inspiration. Various species of vertebrates, such as Rana sylvatica (the wood frog), achieve a thermodynamically stable, noninjurious frozen state at high subzero storage temperatures ranging from −6 to −22 °C. Using cryomicroscopic analysis, researchers have detailed the mechanisms of ice propagation utilized by freeze-tolerant wood frogs in nature . In this study, micrographs of liver slices showed continuous ice formed along the vasculature with the parenchyma remaining ice-free and considerably shrunken because of cellular dehydration.…”
Section: Introductionmentioning
confidence: 76%
“…Various species of vertebrates, such as Rana sylvatica (the wood frog), exhibits the ability to survive long periods of time in a partially frozen state with the whole animal, including every single organ demonstrating the ability to live in the presence of extracellular ice without injury . It has been shown that subarctic populations of wood frogs can tolerate temperatures close to −18 °C, although temperature ranges can vary between −5 and −22 °C. …”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the strategy adopted by the arctic wood frog for high-subzero survival in a partially frozen state, there is extensive evidence that mammalian organ banking might be better served by freeze avoidance rather than freeze tolerance [108, 112], which is also employed in nature. A third option is to leverage the strengths of these two approaches for nonfrozen subzero storage in thermodynamic equilibrium.…”
Section: High-subzero Preservationmentioning
confidence: 99%
“…One good example from the at least 45 animals that can survive long periods of time at high-subzero temperatures in a state of “suspended animation” is the wood frog ( Rana sylvatica ), surviving with 65–70% of the total body water as extracellular ice [112]. One of the most critical strategies for freeze tolerance involves the synthesis of high amounts of low-molecular-weight carbohydrates (glucose in wood frogs), which provide colligative resistance to detrimental decreases in cell volume while also serving to stabilize the phospholipid bilayer of membranes and to restrict the formation of intracellular ice [112-114].…”
Section: High-subzero Preservationmentioning
confidence: 99%
See 1 more Smart Citation